1996
DOI: 10.1097/00005537-199610000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Tuberculosis in HIV‐Infected Patients: A Difficult Diagnosis

Abstract: Unrecognized laryngeal tuberculosis (TB) poses a significant hazard to otolaryngologists. However, the changing manifestations of TB in patients with human immunodeficiency virus (HIV) infection can make its diagnosis difficult. In our population of 146 patients with TB involving the head and neck, HIV infection was present in 70 cases (48%). The prevalence of laryngeal TB in this population was 5.5% (8 patients). Concomitant HIV infection was present in 2 (25%) of 8 patients with laryngeal TB. A delay in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
4
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 8 publications
4
22
4
4
Order By: Relevance
“…13,14 In the present two cases, both the lesions were restricted to unilateral vocal cord superior surface without involving any other area of the larynx. However, in both the cases, the supraglottic laryngeal mucosa showed marked congestion, which is similar to that observed by Singh et al 9 In a study of tubercular laryngitis in 14 patients, Ozüdogru et al 12 had observed that glottal closure presented an irregular shape during treatment, and later became spindle shaped along its entire length. They had also noted the absence of mucosal wave in the posttreatment period, which is contrary to our finding of a normal mucosal wave and normal glottal closure after completion of treatment.…”
Section: Ijoplsupporting
confidence: 83%
See 1 more Smart Citation
“…13,14 In the present two cases, both the lesions were restricted to unilateral vocal cord superior surface without involving any other area of the larynx. However, in both the cases, the supraglottic laryngeal mucosa showed marked congestion, which is similar to that observed by Singh et al 9 In a study of tubercular laryngitis in 14 patients, Ozüdogru et al 12 had observed that glottal closure presented an irregular shape during treatment, and later became spindle shaped along its entire length. They had also noted the absence of mucosal wave in the posttreatment period, which is contrary to our finding of a normal mucosal wave and normal glottal closure after completion of treatment.…”
Section: Ijoplsupporting
confidence: 83%
“…In the presence of acquired immunodeficiency syndrome, the clinical presentation becomes confusing. 9 Also, in the Indian scenario, very often, with an associated history of oral habits like tobacco intake, smoking, etc., laryngeal tuberculosis mimics a malignant lesion of the larynx.…”
Section: Introductionmentioning
confidence: 99%
“…8 HIV infected patients generally have increased risk of otorhinolaryngeal tuberculosis. 10 But in our study, only 3 out of 27 patients were found to be HIV positive.…”
Section: Discussioncontrasting
confidence: 58%
“…Indeed, the resurgence of tuberculosis is attributed to the increased prevalence of immunodeficiency states. Singh et al [11] reported that in his study HIV infection had accompanied 25% of the cases of laryngeal TB. Every patient with TB should be screened for HIV.…”
Section: Discussionmentioning
confidence: 90%